How to study for standardized tests - Sefcik, Donald J.; Bice, Gillian; Prerost, Frank (Jones & Bartlett Learning, 2013)
"The book focuses on the test-taking strategies students must master in order to excel on exams. This valuable guide is a great tool for students preparing to take their national boards as well as practitioners studying for a recertification exam. It focuses on three key variables: the test, you, and various study resources, methods, and technqiues. This detailed guide describes and explains how to work most effectively and efficiently in a timed environment while reducing the impact of test anxiety in addition to providing techniques that will help you prepare for the exam and select the best answers."